1988
DOI: 10.1002/jts.2490010208
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic stress in survivors of an airplane crash‐landing: A clinical and exploratory research intervention

Abstract: Post-traumatic stress in 30 male survivors of an airplane crash-landing was studied through interviews and questionnaires based on a nonpathological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 11 publications
3
35
0
2
Order By: Relevance
“…Further, our study of these survivors indicates that psychological consequences may remain after 10 years. Our results in Study 1 were nearly the same as those of the Kegworth air disaster [8], but provided a striking contrast to Sloan's result [9], in which most passengers recovered in only a few months. However, the disaster reported by Sloan was a non-fatal accident, and all passengers belonged to the same college sport club.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Further, our study of these survivors indicates that psychological consequences may remain after 10 years. Our results in Study 1 were nearly the same as those of the Kegworth air disaster [8], but provided a striking contrast to Sloan's result [9], in which most passengers recovered in only a few months. However, the disaster reported by Sloan was a non-fatal accident, and all passengers belonged to the same college sport club.…”
Section: Discussionsupporting
confidence: 57%
“…Those who saw injured or dead people at the scene, sustained less severe injuries, or were under 35 years of age were significantly more likely to develop PTSD. Sloan [9] followed-up 30 survivors of a nonfatal airplane crash and found high levels of stress in the following months.The Garuda Indonesia air disaster in Japan occurred in 1996. Three passengers died and 108 were injured.…”
mentioning
confidence: 99%
“…One study found a significant decline from 54% in the first month after an airplane crash-landing in Alabama to 10-15% one year after the disaster (Sloan, 1988). Similarly, rapid declines in the prevalence of PTSD over time were documented after the USS Iowa gun turret explosion (Ursano et al 1995), the Piper Alpha oil rig disaster (Alexander, 1993), and the Lockerbie disaster (Scott et al 1995).…”
Section: Studies Of Technological Disastersmentioning
confidence: 99%
“…Riddell and Clouse (2004) describe a second reason for why a temporary object is needed as a protective shield in the face of trauma. A radically-altered sense of the relationship between self and others occurs in the immediate aftermath of catastrophic events, oftentimes characterized by feelings of detachment or estrangement from others (Sloan, 1988), and a sense of time having changed and the event or oneself feeling unreal (Marmar et al, 1994;Cardena & Spiegel, 1993). On the other hand, desperate efforts to rescue others are sometimes observed.…”
Section: Emotional Traumamentioning
confidence: 99%